Gamma-glutamyl transferase is an indicator of gestational diabetes mellitus (Bangladesh Medical Journal, 2016)
Increased gamma-glutamyl transferase (GGT) is associated with gestational diabetes mellitus (GDM) and type 2 diabetes mellitus in pregnant women. This cross sectional study was conducted in the Department of Clinical Pathology in collaboration with Department of Obstetrics and Gynecology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka from March 2014 to February 2015 to assess the GGT as an indicator of GDM. Total 66 pregnant women were enrolled in this study in the Department of Obstetrics and Gynecology, BSMMU. Total 33 cases were considered as Group I (GDM) and 33 controls were Group II (normal healthy pregnant women). Two ml of blood was collected in plain test tube from each patient. Gestational diabetes mellitus were diagnosed by FBS and 2hr after 75g glucose in this study as cases. Normal healthy pregnant women was included in this study as control. GGT was higher in GDM group compared to normal healthy pregnant women (30.60±7.78 vs. 16.45±4.97, p